THE LEGALITY PRINCIPLE IN PROTECTING THE INTERESTS OF VICTIMS IN ARTICLE 1, PARAGRAPH (1) OF THE CRIMINAL CODE - Sari, Clara Mega Kharisma; Sholehuddin, M. (jfpublisher, 2022)
The principle of legality is needed to prosecute acts that cause extraordinary harm to victims, which the action have not been or are not prohibited by criminal law. In Indonesia, the legality principle contained in Article 1 paragraph (1) already has a draft for amendments to the previous article. In the 2010 Draft Law, the Criminal Code Bill still maintains the existence of the principle of legality as a fundamental principle for the enforceability of criminal law. This research aims to find out the implementation of legality principle in protecting the victims and perpetrators’ interest along with the right justice for the criminals. This research is normative legal research that aimed at legal concepts, statutory regulations, and other legal materials. This research is conceptual and statutory approach through Criminal Code (WvS), Criminal Procedure Code, and the 1945 Constitution to understand the basic concept of legality contained in Criminal Code article on law enforcement and justice. In this research, it found that the existence of legality principle is very necessary to protect citizens’ rights from arbitrary government in their decision-making. It can be concluded that the meaning contained in legality principle is to provide a protection for perpetrators from arbitrary authorities as well as a limiting function for government to not make decisions injudiciously. This means that the legality principle only regulates the relationship between the perpetrator and government, while the relationship between victim and government is not regulated in it that resulted in no protection for victims.